Kecemasan Antaretnis Sebagai Mediator Kontak Antaretnis Dengan Prasangka Etnis Pada Mahasiswa - Ni Nyoman Shantti Triana S. M. Wantera; Marselius Sampe Tondok (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2023)
Ethnic diversity in Indonesia often causes interethnic conflict, including among students of different ethnicities. Stereotypes and prejudices can lead to conflict. In intergroup relations based on social identity, there are several factors that influence prejudice, including intergroup contact and intergroup anxiety. This study aims to determine the relationship between interethnic contact and interethnic prejudice mediated by interethnic anxiety in Javanese students towards ethnic students from NTT. This research was conducted using a cross-sectional survey design with a total of 386 students in the city of Surabaya as participants who were obtained by accidental sampling technique. There are three measurement tools used to collect data, namely the General Intergroup Contact Quantity and Quality (CQCQ) scale, the Intergroup Anxiety Scale (IAS), and the RIVEC Prejudice Scale which all have been adapted according to the context of this study. The data analysis technique used is the mediation test. The results showed that interethnic anxiety acted as a partial mediator in the relationship between interethnic contact and interethnic prejudice. Nonetheless, it was found that the mediating function of interethnic anxiety exerts a greater influence than the direct effect of interethnic contact on ethnic prejudice. The findings of this study can become the basis for the development of research and interventions to reduce intergroup prejudice.